Stance Marking and Register in Middle English Charms - Alonso-Almeida, Francisco (Studia Anglica Posnaniensia, 2009)
This paper explores the expression of stance in a corpus of Middle English charms of the fifteenth century. All the charms have a healing function, and they are used whenever standard herbal remedies are ineffective. The sources from where the texts have been taken are various, all of them from edited printed material. The study of language use and the expression of personal attitude and evaluation have been studied earlier, both synchronically (Chafe 1986; Hunston 1994) and diachronically (Kytö 1991; Salager-Meyer - Defyves 1998). However, to my knowledge, the medieval English charm has not been the object of any previous account. This study of stance in charms has implications for language register, and shows both the relationship of the authors and their texts, and the authors and their audience.